Navigating Social Spaces: Armed Mobilization and Circular Return in Eastern DR Congo. (6th September 2020) - Vlassenroot, Koen; Mudinga, Emery; Musamba, Josaphat
Abstract: This article discusses the social mobility of combatants and introduces the notion of circular return to explain their pendular state of movement between civilian and combatant life. This phenomenon is widely observed in eastern Democratic Republic of Congo (DRC), where Congolese youth have been going in and out of armed groups for several decades now. While the notion of circular return has its origins in migration and refugee studies, we show that it also serves as a useful lens to understand the navigation capacity between different social spaces of combatants and to describe and understand processes of incessant armed mobilization and demobilization. In conceptualizing these processes as forms of circular return, we want to move beyond the remobilization discourse, which is too often connected to an assumed failure of disarmament, demobilization, and reintegration processes. We argue that this discourse tends to ignore combatants' agency and larger processes of socialization and social rupture as part of armed mobilization.